Evidence for Late Triassic crustal suturing of the Central and Southern Pamir. Issue 3 (1st June 2020) - Villarreal, Dustin P.; Robinson, Alexander C.; Carrapa, Barbara; Worthington, James; Chapman, James B.; Oimahmadov, Ilhomjon; Gadoev, Mustafo; MacDonald, Brian
Highlights: The Southern Pamir and Central Pamir accreted to the Northern Pamir by the end of the Triassic. The Central and Southern Pamir are the western extension of the Qiangtang terrane of Tibet. The Northern Pamir was elevated prior to the accretion of the Central and Southern Pamir. Abstract: The timing of closure of the Paleotethys and Rushan ocean basins and suturing of Gondwanan crustal fragments in the Pamir is not well resolved. Whereas the Central Pamir terrane is generally interpreted to have collided with the Northern Pamir terrane at the end of the Triassic, closure of the Rushan ocean and collision of the Southern Pamir terrane has been interpreted to be either broadly coeval (i.e., Late Triassic–Early Jurassic ~200 Ma) or have occurred significantly after closure of the Paleotethys in the Late Jurassic. New petrographic analyses and detrital zircon U-Pb data of the Lokzun Group Flysch and the terrigenous Darbasatash Group of the Southern Pamir terrane advocate for coeval terrane accretion of the Central and Southern Pamir terranes by the Latest Triassic. The Rhaetian Lokzun Group Flysch and the Early Jurassic Darbasatash Group have well-constrained stratigraphic ages and lie directly below and above a post-Cimmerian orogeny angular unconformity, respectively. Petrographic results for both successions indicate a recycled orogenic belt source, and detrital zircon age spectrum for both contain two prominent Phanerozoic age populations: an Early Silurian–Early Devonian (~440–408 Ma) and a Carboniferous Late Triassic (~350–222 Ma). These results suggest sediment was sourced from the Karakul-Mazar terrane, located in the northern Pamir, which requires closure of the Paleotethys and Rushan ocean basins and initial collision with the Central and Southern Pamir terranes by the end of the Late Triassic. Furthermore, these results suggest that the Northern Pamir terrane was topographically elevated relative to the surrounding terranes throughout the early Mesozoic.